Futebol na escola: uma proposta além do jogo - Munhoz, Raquel Fantinelli (Universidade Federal de São Carlos, 2013)
The present study consists of an action research that aimed to action to implement a program of classes on the socio-cultural aspects of football in a 9th grade of elementary school and as a research objective to reflect on the results of this proposal. As instruments of data collection, diaries were used and the focus group. In class the following socio-cultural themes were addressed: football and politics; football, gender and work; football, gift and talent. The results found were divided into three categories: football and society: reports and reflections on interventions; student participation and resistance in relation to classes and themes; perceptions of teacher-researcher about how to teach classes and also the classes that took place in the study. The results indicate the importance of addressing socio-cultural themes from the perspective external logic of sports in Physical Education classes, as students manage to make a relation of the themes with the daily life, however, these students do not showed interest in deepening the themes, showing a commitment only immediate about what was discussed, already in relation to the participation and resistance of the students, observe that the students participated in the discussions effectively and that they knew how to talk on the themes, but within a system in which the “free classes” are already implemented, the students indicated they prefer the “class” model that we present in our interventions. Regarding the perceptions as a teacher-researcher regarding the classes, the importance of systematic teacher intervention in the students' learning process, as well as the approach of all dimensions of content in classes. Furthermore, in this category it was possible to identify that there is a need to introduce students to Education Physics as a curricular component and not just as a moment of leisure and rest.
Football at school: a proposal beyond the game
Keywords: Educação Física escolar; Futebol; Lógica externa; Temas socioculturais; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM